(untitled) (Bangladesh Critical Care Journal, 2024)
Background: Parkinson’s disease is a chronic, progressive, neurodegenerative disease. Various factors have been attributed to the development and progression of the diseaseover the years. Uric acid is the final oxidation product of purine metabolism with potent antioxidant properties, which could play an important role in reducing the risk of development of Parkinson’s disease (PD) as well as it could have a role in delaying the progression of Parkinson’s disease (PD). Aim: This study aims at evaluating the role of serum uric acid level in clinical progression of Parkinson’s disease. Methods: This cross-sectional study was conducted among 70 patients of Parkinson’s disease attending the outpatient department and meeting the inclusion criteria. All the clinical and biochemical data were collected and analyzed by SPSS. Mean serum uric acid levels were compared between different stages of Parkinson’s disease. A p value of less than 0.05 was considered as significant. Result: Mean age of the patients with Parkinson’s disease was 62.25 ± 8.56 years with a male to female ratio of 1.12:1. Regarding the clinical presentation of the patients, it was observed that 16 (22.9%) patients had combination of tremor, hypokinesia, rigidity and postural imbalance, 18 (25.7%) had tremor, hypokinesia & rigidity and 36 (51.4%) had tremor and rigidity. It was observed that 24.3% of the patients had sensory, sleep and cognitive disorder, 21.4% patients had sleep and cognitive disorder, 2.9% patient had disorder in sleep and anosmia, 8.6% patients had only sleep disturbance, 17.1% had only cognitive disturbance but 25.7% had no non-motor symptoms. Majority (61.4%) patient’s disease duration was 1-5 years. The mean duration of disease was found 6.34±5.53 years. Majority 34 (48.6%) patients were in stage II, 19 (27.1%) were in stage III, 5 (10.0%) were in stage IV and 12 (17.1%) were in stage V. Mean serum uric acid was found to be 3.45±1.26mg/dL (2.0-5.8) in male and 3.36±0.81mg/dL(2.1-5.8) in female patients.Serum uric acid level steadily reduced with the severity of PD which is statistically significant. Advanced stages of parkinson’s disease were associated with significantly lower levels of serum uric acid. The difference between the stages were statistically significant (p=0.007). Conclusion: This study shows a negative association between serum uric acid level and the severity of Parkinson’s disease. The level of serum uric acid decreased with the disease progression. This study added evidence consistent with an association between serum uric acid level and the severity of Parkinson’s disease. This finding pushes us to emphasize on the role of uric acid levels on the Parkinson’s disease. Bangladesh Crit Care J March 2024; 12 (1): 18-24